Comparative Accuracy Analysis of GNSS Observation for Positioning with A Combination of GPS, GLONASS, and BEIDOU Satellite - Ristanto, Wahyu; Khomsin, Khomsin; Anjasmara, Ira Mutiara (IPTEK Journal of Proceedings Series, 2019)
GNSS (Global Navigation Satellite System) is a term used for the entire global navigation satellite system that already operate or are in the planning. some of them namely GPS, GLONASS, and BeiDou. Errors due to less powerful satellite geometry when data retrieval, in teoritik can be resolved with receiver technological advances that was able to capture many of satellite signals. Hi Target V30 is one of GNSS receivers are able to catch GPS, GLONASS and BeiDou signal, with more satellite signals that can be received are expected to improve the accuracy of positioning. From this study is known that the use of BEIDOU satellite not too influential on the GPS satellites, but will add to the accuracy of the GLONASS satellite. This is demonstrated by the existence of a reduction in average value on difference coordinates and RMS error reduce from 1,068 m into 0371 m. The use of GPS + GLONASS + BEIDOU and GPS + GLONASS satellite combinaton provide the best accuracy with the RMS value of the error remain in the millimeter, while the use of GLONASS satellites alone give the worst accuracy among the strategies with the value of RMS error visible to reach 0585 m on baseline C2.